2003
DOI: 10.1063/1.1554775
|View full text |Cite
|
Sign up to set email alerts
|

Thermomigration in Pb–Sn solder joints under joule heating during electric current stressing

Abstract: Electromigration of solder joint under high dc current density is known as a reliability concern for the future high-density flip chip packaging and power packaging. Biased mass diffusion within solder joint from cathode to anode under high dc current density is observed in these experiments. In this letter, the experiments on flip chip solder joints under dc current stressing are conducted and thermomigration due to the thermal gradient in the solder joint caused by joule heating is reported. A three-dimensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
96
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 236 publications
(99 citation statements)
references
References 3 publications
3
96
0
Order By: Relevance
“…The entire sample fixture was immersed in a heat-conductive oil bath to minimize temperature gradient and temperature rise, as both are known to induce thermomigration in solder joints. 10 The current density at which the solder joint becomes liquid is taken as the critical current density. Using a high magnification microscope, we tested multiple samples, and the average critical current density was determined to be 2.8 · 10 4 A/cm 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The entire sample fixture was immersed in a heat-conductive oil bath to minimize temperature gradient and temperature rise, as both are known to induce thermomigration in solder joints. 10 The current density at which the solder joint becomes liquid is taken as the critical current density. Using a high magnification microscope, we tested multiple samples, and the average critical current density was determined to be 2.8 · 10 4 A/cm 2 .…”
Section: Methodsmentioning
confidence: 99%
“…He concluded that a flux of salt was generated by a temperature gradient, which results in a concentration gradient in steady state conditions (Platten, 2006). Ye et al (2003e) showed that the same process also takes place in solder alloys. Experimental studies suggest that the effect of thermomigration on solder joint reliability is as serious as that of electromigration (Ye et al, 2003b;2003c;2003e;Huang et al, 2006;Roush and Jaspal, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…They found that Sn moved to the hot end while Pb moved to cold end. Ye et al (2003e) reported thermomigration may assist electromigration if the higher temperature side coincides with the cathode side, and counter electromigration if the hot side is the anode side.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations